The Inuit Population of Northern Quebec: Present Situation, Future Trends - Robitaille, Norbert; Choinière, Robert (Anthropologica, 2022)
The Inuit population of Northern Quebec, 5,000 approximately in 1981, is scattered in fourteen villages along the coasts of Hudson Bay, Hudson Strait and Ungava Bay (Figure 1). None of these villages had, in 1981, more than a thousand Inuit and the proportion of non-Inuit in most of these villages was negligible. The purpose of this paper is to compare the present demographic situation of the Inuit of Northern Quebec, to its past trends and likely future. We also included information concerning the Inuit of the Northwest Territories, and the total population of Quebec for comparison.